The Use of Typologies in Tourism Planning: Problems and Conflicts - Harry Coccossis; Mary Constantoglou (European Regional Science Association (ERSA), 2006)
Tourism is a worldwide socioeconomic phenomenon. Its environmental, social and economic aspects have been for years at the center of interest of policy making and research communities. Sustainable tourism is a concept that mainly reflects the need for comprehensive analysis and integrated planning and management of tourism. In this respect it is important to develop appropriate analytical and policy tools for tourism, particularly to reflect the different conditions, characteristics and patterns of tourism development in geographic space. Spatial typologies for tourism can be an effective tool for this purpose. The main scope of this paper is to analyze the concept, the need and the use of typologies in the overall planning process and in tourism planning process specifically.
Keywords: 330